Penggunaan Model Pembelajaran Snowball Throwing untuk Meningkatkan Hasil Belajar Siswa pada Pelajaran Matematika Materi Bilangan Bulat pada Siswa Kelas IV SD Negeri 066665 Medan Denai Tahun Ajaran 2023/2024 - Reflina Sinaga; Repidawati Repidawati; Sri Heriyanti; Eva Novita; Romauli Sinaga; Jaiyah Jaiyah (Journal on Education, 2024)
The problem investigated in this study is the low student learning outcomes in Mathematics subject matter of whole numbers in class IV SD Negeri 066665 Medan. As a result of the teacher not optimally using a varied teaching model in the learning process. The research conducted was Classroom Action Research with the research subjects being fourth grade students of SD Negeri 066665 Medan Denai. This research took place in two cycles. In cycle 1 and II, Mathematics learning was carried out using the Snowball Throwing learning model. The research method used is quantitative method. From the results of the study, it was obtained that the implementation of learning by using the Snowball Throwing learning model in mathematics lessons on integer material in class IV at SD Negeri 066665 Medan in the 2023/2024 school year had reached the good category, with details of teacher activity observation cycle I (60%) increased to (80%) and observation of student activity cycle I (68%) cycle II increased to (86%). There is an increase in student learning outcomes after using the Snowball Throwing learning model on whole number material in class IV SD Negeri 066665 Medan in the 2023/2024 academic year, classical student learning completeness in cycle I (65%) and increased in cycle II to (88%) and the average student score in cycle I (69.6) and increased in cycle II to (80.6). Based on the results of research conducted by researchers with two cycles, it can be concluded that the use of the Snowball Throwing learning model can improve student learning outcomes in Mathematics lessons on integer material at SD Negeri 066665 Medan.